A Samaritan State Revisited Historical Perspectives on Canadian Foreign Aid - Donaghy, Greg; Webster, David (Beyond Boundaries: Canadian Defence and Strategic Studies, 2019)
Canada's foreign aid programs are an area of ongoing interest, yet there is little knowledge of Canada's 70-year aid history, the historic forces that have shaped Canadian aid policy, and the many complex factors that affect Canada's future foreign aid policy. A Samaritan State Revisited brings together a refreshing group of emerging and leading scholars to reflect on the history of Canada's overseas development aid. Addressing the broad ideological and institutional origins of Canada's official development assistance in the 1950s and specific themes in its evolution and professionalization since the 1960s, this collection is the first to explore Canada's history with foreign aid with this level of interrogative detail. Extending from the 1950s to the present and covering Canadian aid to all regions of the Global South, from South and Southeast Asia to Latin America and Africa, these essays embrace a variety of approaches and methodologies ranging from traditional, archival-based research to textual and image analysis, oral history, and administrative studies. A Samaritan State Revisited weaves together a unique synthesis of governmental and non-governmental perspectives, providing a clear and readily accessible explanation of the forces that have shaped Canadian foreign aid policy